IL-33 Protects Mice against DSS-Induced Chronic Colitis by Increasing Both Regulatory B Cell and Regulatory T Cell Responses as Well as Decreasing Th17 Cell Response. (13th November 2018) - Zhu, Jun-feng; Xu, Ying; Zhao, Jian; Li, Xue; Meng, Xinrui; Wang, Tian-qi; Zou, Ben-yao; Zhao, Peng-yan; Liu, Qi; Lu, Chang-long; Zheng, Fang-liang; Liu, Hong-sheng
Abstract : Background . Previously, we have reported that IL-33 functioned as a protective modulator in dextran sulfate sodium- (DSS-) induced chronic colitis by suppressing Th17 cell response in colon lamina propria and IL-33 induced both regulatory B cells (Bregs) and regulatory T cells (Tregs) in mesenteric lymph nodes (MLNs) of mice with DSS-induced acute colitis. Moreover, we speculated that IL-33 would promote the Treg or Breg responses leading to the attenuation of DSS-induced chronic colitis. So, we investigated the role of IL-33 on Bregs and Tregs in the MLN of DSS-induced chronic colitis mice. Methods . IL-33 was administered by intraperitoneal injection to mice with DSS-induced chronic colitis. Clinical symptoms, colon length, and histological changes were determined. The production of cytokines was measured by ELISA. The T and B cell subsets were measured by flow cytometry. The expression of mRNA of transcription factors was measured by quantitative real-time PCR. Results . We show that IL-33 treatment increases both Breg and Treg responses in the MLN of mice with DSS-induced chronic colitis. Moreover, IL-33 treatment also decreases Th17 cell response in the MLN of mice with DSS-induced chronic colitis. Conclusion . Our data provide clear evidence that IL-33 plays a protective role in DSS-induced chronic colitis, which is closely related to increasing Breg and Treg responses in the MLN of mice as well as suppressing Th17 cell responses.